2017
DOI: 10.1038/s41598-017-10155-x
|View full text |Cite
|
Sign up to set email alerts
|

CD2068 potentially mediates multidrug efflux in Clostridium difficile

Abstract: Clostridium difficile is a major cause of antibiotic-associated diarrhea and the treatment thereof becomes more difficult owing to a rise of multidrug resistant strains. ATP-binding cassette (ABC) transporters are known to play a crucial role in the resistance to multiple antibiotics. In this study, the potential contribution of an ABC transporter in C. difficile multidrug resistance was investigated. The expression level of the cd2068 gene in C. difficile encoding an ABC transporter was up-regulated following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Upon review of these additional three articles, they did not meet the inclusion criteria. After a full-text review, the same eight articles were identified for inclusion through either literature search strategies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Upon review of these additional three articles, they did not meet the inclusion criteria. After a full-text review, the same eight articles were identified for inclusion through either literature search strategies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The protein is encoded from cd630_20680 and showed a considerable degree of sequence homology, up to 67% identity to YkpA, an uncharacterized ATPase protein in sub-family 3 of B. subtilis . Although the YkpA was assumed to not fully function in B. subtilis [32] , the CD2068 was previously characterized to confer multidrug resistance using heterologous expression in E. coli and gene disruption and complementation in C. difficile [59] . It appears possible that this protein may couple with other membrane protein(s) for transport activity [59] .…”
Section: Resultsmentioning
confidence: 99%
“…Although the YkpA was assumed to not fully function in B. subtilis [32] , the CD2068 was previously characterized to confer multidrug resistance using heterologous expression in E. coli and gene disruption and complementation in C. difficile [59] . It appears possible that this protein may couple with other membrane protein(s) for transport activity [59] . Therefore, a comprehensive study with direct assays of the NPs in sub-family 3 would be helpful to fully understand the function of this class of transporters.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in unsuccessful cases, FMT treatment upregulated the excretion of metabolites that are members of the ABC transport system superfamily, which contains amino acids, choline, putrescine, and spermidine. Given that ABC transporters are involved in the transport of a variety of substances ranging from simple ions to large molecules as well as signal transduction, drug and antibiotic resistance, and antigen presentation [ 7 , 44 ], it is possible that these transporters function abnormally in unsuccessful cases. The gene expression associated with ribosomal translation, amino acid metabolism, and carbohydrate metabolism is reduced in calves suffering from hemorrhagic diarrhea [ 3 , 6 , 13 ]; therefore, in additional FMT studies, it will be important to identify the key microbial clusters that regulate intestinal metabolites.…”
Section: Discussionmentioning
confidence: 99%